The antimicrobial protein S100A12 identified as a potential autoantigen in a subgroup of atopic dermatitis patients. Issue 1 (31st January 2019) - Mikus, Maria; Johansson, Catharina; Acevedo, Nathalie; Nilsson, Peter; Scheynius, Annika
Abstract: Background: Atopic dermatitis (AD) is a complex heterogeneous chronic inflammatory skin disease. Specific IgE antibodies against autoantigens have been observed in a subgroup of AD patients, however, little is known about IgG‐auto‐reactivity in AD. To investigate the presence of autoreactive IgG antibodies, we performed autoantibody profiling of IgG in patients with AD of different severities and in healthy controls (HC). Methods: First, we performed an untargeted screening in plasma samples from 40 severe AD (sAD) patients and 40 HC towards 1152 protein fragments on planar antigen microarrays. Next, based on the findings and addition of more fragments, a targeted antigen suspension bead array was designed to profile a cohort of 50 sAD patients, 123 patients with moderate AD (mAD), and 84 HC against 148 protein fragments representing 96 unique proteins. Results: Forty‐nine percent of the AD patients showed increased IgG‐reactivity to any of the four antigens representing keratin associated protein 17‐1 (KRTAP17‐1), heat shock protein family A (Hsp70) member 4 (HSPA4), S100 calcium binding proteins A12 (S100A12), and Z (S100Z). The reactivity was more frequent in the sAD patients (66%) than in those with mAD (41%), whereas only present in 25% of the HC. IgG‐reactivity to S100A12, a protein including an antimicrobial peptide, was only observed in AD patients (13/173). Conclusions: Autoantibody profiling of IgG‐reactivity using microarray technology revealed an autoantibody‐based subgroup in patients with AD. The four identified autoantigens and especially S100A12 could, if characterized further, increase the understanding of different pathogenic mechanisms behind AD and thereby enable better treatment.